Analysis of the rough contact in axisymmetric upsetting - Cui, Yu (Trinity College Dublin. School of Engineering. Mechanical & Manufacturing Engineering, 2007)
Characterization of surface roughness is important in the frictional behavior of two contact surfaces. In general, it has been found that friction increases with average roughness. The prediction of friction and stress/ strain/ deformation is of interest in the friction-sensitive process such as aximmetric upsetting. However, the classical friction laws, such as Coulomb's law and its extension - Coulomb-Amonton's law, Coulomb-Orowan are found to be coarse and oversimplified especially in the presence of surface complexities. The first objective of this project is to examine the microscopic evolution of the upsetting process with Finite Element software, with the focus on the interaction between the tool asperity and the plastic wave. The second objective is to evaluate Coulomb?s law and Plastic wave theory based on small-scale numerical models. The third objective is to implant the friction laws and prior findings into the experiment-size Finite Element models so that comparison between simulation and expriments could be made. This project is a contribution to the definition of a new friction test for bulk forming processes.
Keywords: axisymmetric upsetting; Finite element analysis; surface roughness; plastic wave model